The Role of Social Media as a Measures of Information Delivery to Reduce the Risk of Flood Disasters in Kecamatan Pasar Kliwon, Surakarta City in 2020 - Mikael Dafit Adi Prasetyo; Chatarina Muryani; Gentur Adi Tjahjono (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
This study aims to perceptions and responses to flood disaster risk reduction social media in Pasar Kliwon District, Surakarta City, 2020. Utilization of whatsapp social media as a means of delivering information to the public in an effort to reduce disaster risk flooding in Pasar Kliwon Subdistrict, Surakarta City, 2020. the impact of the use of whatsapp social media as a means of delivering information on community efforts to reduce the risk of flood disasters in Pasar Kliwon District, Surakarta.The results of the study are as follows: Perception of flood disaster in Pasar Kliwon Subdistrict, if viewed from the potential of the disaster, it can be categorized as very large. For flood disaster vulnerability is also categorized as flood disaster prone. And disaster mitigation is carried out in the form of responsiveness and preparedness from stakeholders. Here the use of social media as a means of delivering flood disaster information.